Підвищення рівня обслуговування систем управління запасами шляхом інтеграції процесів транспортної логістики - Алешинский, Евгений Семенович; Мещеряков, Василий Владимирович; Бондаренко, Антон Павлович (НТУ "ХПИ", 2017)
Рассмотрены подходы к функционированию систем транспортной логистики и управления запасами. Приведены некоторые этапы форми-рования системы управления запасами. Для повышения уровня обслуживания систем, где одним из наиболее проблемных мест является низкий уровень управления и отсутствие прочных связей, использованы параметры логистики запасов, на которые оказывают влияние транспортно-складские процессы. Использованы параметры надежности перевозчиков, доступности необходимого количества подвижного состава в регионе, функциональный цикл выполнения заказа при пополнении запасов.

The object of the research is the process of cooperation between the transport system and the inventory management system. One of the most prob-lematic places of the research object is the low level of management and the lack of strong links between logistics systems, in particular: the lack of permanent transport company, ineffective distribution of own vehicles, and low reliability of transport. For determining the locations of mutual integration of processes next scientific methods are used: classification of risks, theory of reliability, analysis of kinds and consequences of refuses, probability and queuing, system theory. During integration of processes of transport logistic in the sys-tem of purchases used: theory of making decision, theory of decision of inventor tasks, theory of optimization. Identified points of mutual integration of processes the parameters of calculation - time of implementation and size of order became that are de-termined. These parameters are chosen by reason of account of time and expenses on transporting at their calculation. Through the terms of reliability and availability the technological process of work of transport is partly integrated. The relationship between some elements of systems is defined, such as the relationship between the point of order and availability, between the order size and reliability. We have the example shows that the cost of freight to carry 30,000 UAH. advantageous to use option 1, since this option has the lowest cost (23 760 UAH.), despite the high cost, and empty runs. Further possibilities of the use of similar syntheses are educed: methods of increase of cooperation of the systems, use of mutual advantages.
Increasing service level of reserve management systems by integration of transport logistics processes
Keywords: логистика; перевозчик; надежность; состав подвижной; logistic processes; transport company; reliability; vehicle